EFFECTIVENESS OF BUDGET ABSORPTION IN KABUPATEN PONOROGO IN 2011-2015 - Febryan, Aditya Oriza (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Using data from 2011-2015, this study aims to analyze the performance of the government Ponorogo using five variables, namely the ratio of: (1) Independence, (2) Effectiveness, (3) Growth, (4) Efficiency and (5) Variance After knowing the data about the finances of Ponorogo, then the data will be processed by some formula to determine the performance of the government's performance in managing finances in PonorogoBy knowing the performance of the government in managing the financial area, then we can know what are things that need to be repaired and maintained in the public financial management system daerah.This is can also be taken into consideration and input for local governments to be better in the futureKeywords: independence, effectiveness, growth, efficiency, variance